Papaya Fruit Supply Chain System in Surabaya City: Towards a Better Food and Nutrition Urban Governance - Lamatungga, Kiki Ekiawan; Abbas, Hasriwiani Habo; Muhammad Nasir; Arsyidik (Window of Health : Jurnal Kesehatan, 2024)
Papaya (Carica papaya Linn) is a tropical fruit with high economic and nutritional value. Indonesia was the fourth biggest papaya producer in the Asian continent from 2008 to 2018, and East Java was the primary contributor. Papaya has complex chemical components such as protein, carbohydrates, fat, fiber, minerals, and vitamins. However, its supply chain system faces challenges such as postharvest issues, processing and transportation, and low consumption. This study aimed to determine the papaya fruit supply chain system in Surabaya City to reform the existing food and nutrition action plan, which has not yet been fully implemented. With a toolkit from FAO called RUFSAT (Rapid Urban Food System Assessment Tool), the food system was developed with a primary concern on papaya commodities. Results indicated that the papaya supply chain in Surabaya is comprised of three channels: farmer to collector, wholesaler/distributor, retailer, and consumer. Acquisition and distribution of papaya still suffered from losses, food safety, transportation handling, packaging issues, and quality assurance practices. In terms of consumption, most households ingested papaya within 1-3 times per week, which is considered inadequate. Effective collaboration among city government agencies is pivotal for addressing supply chain complexities. In addition, integrating papaya with other fruits into urban farming initiatives can help to improve the nutritional status of Surabaya citizens.